2014
DOI: 10.1371/journal.pone.0113256
|View full text |Cite|
|
Sign up to set email alerts
|

Low Message Sensation Health Promotion Videos Are Better Remembered and Activate Areas of the Brain Associated with Memory Encoding

Abstract: Greater sensory stimulation in advertising has been postulated to facilitate attention and persuasion. For this reason, video ads promoting health behaviors are often designed to be high in “message sensation value” (MSV), a standardized measure of sensory intensity of the audiovisual and content features of an ad. However, our previous functional Magnetic Resonance Imaging (fMRI) study showed that low MSV ads were better remembered and produced more prefrontal and temporal and less occipital cortex activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 63 publications
1
35
1
Order By: Relevance
“…First, they extend prior studies on the mechanisms of neurocognitive processing of the high-MSV format (Langleben et al, 2009; Seelig et al, 2014; Wang et al, 2013) to genetic variability, i.e. the DAT1 polymorphism.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…First, they extend prior studies on the mechanisms of neurocognitive processing of the high-MSV format (Langleben et al, 2009; Seelig et al, 2014; Wang et al, 2013) to genetic variability, i.e. the DAT1 polymorphism.…”
Section: Discussionsupporting
confidence: 57%
“…These findings suggest that greater rTPJ response to the high- MSV format is associated with poorer long-term behavioral responsiveness to smoking-cessation messaging. A possible explanation could be that the 10/10 individuals developed a less adaptive processing style that focused on the sensory features of the videos, and thus received less benefit from the anti-smoking information (Langleben et al, 2009; Seelig et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic motion and audio features may indeed be effective in making ads more memorable (Han et al, ). However, stimuli wealth and complexity may otherwise exceed the capacity to assimilate information and result in reduced message retention (Langleben et al, ; Seelig et al, ; Wang et al, ). In our audiovisual experiment, some balance may exist between the advantages and disadvantages of providing more complex information.…”
Section: Discussionmentioning
confidence: 99%
“… Lang, 2006 ). Experimental fMRI work has shown that low-compared to high-MSV persuasive ads are better remembered, elicit increased activity in temporal and prefrontal cortex, and correspond to lower levels of occipital cortex activation ( Seelig et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%